2012
DOI: 10.1111/j.1742-4658.2012.08552.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the conformation of building blocks in curing of barnacle underwater adhesive

Abstract: Barnacles are a unique sessile crustacean that attach irreversibly and firmly to foreign underwater surfaces. Its biological underwater adhesive is a peculiar extracellular multi‐protein complex. Here we characterize one of the two major proteins, a 52 kDa protein found in the barnacle cement complex. Cloning of the cDNA revealed that the protein has no homolog in the nonredundant database. The primary structure consists of four long sequence repeats. The process of dissolving the protein at the adhesive joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 37 publications
0
85
0
Order By: Relevance
“…The high amounts of hydrophobic amino acids found in the cement of D. fascicularis agree with the findings in the cement of B. crenatus, B. perforatus and M. rosa. Naldrett & Kaplan (1997), Kamino (2010) and Kamino et al (2012) stated that hydrophobic interactions rendered the cement matrix insoluble and made it resistant to decomposition by Biofouling 959 marine bacteria (Naldrett 1993). Both qualities are particularly important for Dosima cement because the cement needs stability against mechanical impact while drifting in the sea (Zheden et al unpublished).…”
Section: Discussionmentioning
confidence: 96%
“…The high amounts of hydrophobic amino acids found in the cement of D. fascicularis agree with the findings in the cement of B. crenatus, B. perforatus and M. rosa. Naldrett & Kaplan (1997), Kamino (2010) and Kamino et al (2012) stated that hydrophobic interactions rendered the cement matrix insoluble and made it resistant to decomposition by Biofouling 959 marine bacteria (Naldrett 1993). Both qualities are particularly important for Dosima cement because the cement needs stability against mechanical impact while drifting in the sea (Zheden et al unpublished).…”
Section: Discussionmentioning
confidence: 96%
“…The presence of glycans in the adhesive secretory granules of Hydra has been reported Rodrigues et al (Forthcoming). Several adhesive proteins performing either permanent or temporary adhesion have been found to be glycosylated in other systems, such as in the marine sea stars, barnacles and green mussels (Ohkawa et al 2004; Zhao et al 2009; Hennebert et al 2010; Kamino et al 2012), in freshwater zebra mussels (Rzepecki & Waite 1993), and also in the stick threads secreted by terrestrial velvet worms (Graham et al 2013). Both N- and O-glycosylation were reported, as is the case of N-glycosylation of cp52 k in barnacles, and O-linked glycans primarily to threonine residues in green and zebra mussels Pvfp-1 and Dpfp-1 (Rzepecki & Waite 1993; Ohkawa et al 2004; Zhao et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The spectral features observed by FTIR and XPS are consistent with proteinaceous chemistries. There are multiple proteins associated with the cuticle of Crustacea, including settlement inducing proteins in barnacles (Dreanno et al 2006), but the specific components that could be related to prior biochemical assays of barnacles (Kamino et al 2012), and their relationship to the cuticle membrane, have yet to be identified.…”
Section: Discussionmentioning
confidence: 99%